Nano-buffer controlled electron tunneling to regulate heterojunctional interface emission - Wei Liu (Institue of Optics and Electronics, Chinese Academy of Sciences, 2021)
Interface emission from heterojunction is a shortcoming for electroluminescent devices. A buffer layer introduced in the heterojunctional interfaces is a potential solution for the challenge. However, the dynamics for carrier tunneling to control the interface emission is still a mystery. Herein, the low-refractive HfO2 with a proper energy band configuration is employed as the buffer layer in achieving ZnO-microwire/HfO2/GaN heterojunctional light-emitting diodes (LEDs). The optically pumped lasing threshold and lifetime of the ZnO microwire are reduced with the introduced HfO2 layer. As a result, the interface emission is of blue-shift from visible wavelengths to 394 nm whereas the ultraviolet (UV) emission is enhanced. To regulate the interface recombination between electrons in the conduction band of ZnO and holes in the valence band of GaN, the tunneling electrons with higher conduction band are employed to produce a higher tunneling current through regulation of thin HfO2 film causing blue shift and interface emission enhancement. Our results provide a method to control the tunneling electrons in heterojunction for high-performance LEDs.